Highly Bio‐Based Unsaturated Polyester Resins with Improved Performance by Incorporating Isosorbide into the Polyester Prepolymer. Issue 9 (16th June 2022) - Li, Yong; Qu, Jiehao; Dai, Zenghui; Jiang, Junyi; Fu, Jiajia; Fu, Feiya; Liu, Xiangdong
Abstract: Herein, the successful design of a highly bio‐based family of unsaturated polyester resins (UPRs) is presented, comprising of an isosorbide (ISO) incorporated unsaturated polyester prepolymer (UP) and a reactive diluent of 4‐vinylguaiacol acetyl ester (ACVG). A series of UPs are prepared by copolymerizing ISO with other green monomers, i.e., itaconic acid, ethylene glycol and oxalic acid, in a variation of ISO fraction. The UP/ACVG mixtures exhibit very low viscosity ranging from 2.8 to 3.7 Pa s. After curing at 135 °C to form a network, the resulting thermosets exhibit remarkable improvements in terms of glass transition ( T g, about 131 °C), storage modulus (2564–3342 MPa), and tensile strength (around 76.6 MPa), which are significantly better than the UP thermosets reported in previous works, The incorporation of ISO units into the UPs reveals a favorable effect on thermal stability of the thermosets as well. The best Td5% is measured to be 320.4 °C, and the volatile molecular information collected using a TGA‐GC/MS set suggests that the decomposition mechanism of the cross‐linked resins becomes heat‐resistant due to the ISO incorporation. Moreover, after being reinforced by cotton fabrics, an outstanding compatibility between the ISO containing UPRs and cotton fibers is found to be suitable for composite fabrication. Abstract : The prepared ISO‐based UPs exhibit excellent miscibility with green diluent of ACVG and the combination of ISO‐based UPs and ACVG results in a high Tg.After reinforcement with cotton fabrics, an outstanding compatibility between the resins and cotton fabrics is found to be suitable for composite fabrication.